Time-cost trade-off problem for repetitive activities in construction projects (2017)
One of the principal construction projects objective is to schedule its activities in order to minimize the duration of the project at the lowest possible cost, this is addressed in the time-cost trade-off problem. On the other hand, there is a technique used to schedule construction projects known as Line-of-Balance, which determines the number and size of crews to be employed in each repetitive activity. Existing optimization models are capable of identify, from a set of models, the optimum model for each activity in a repetitive activities project so that the cost is minimized. However this models don't take into account the Line-of-Balance scheduling technique, which is ideal for construction projects. In this order of ideas this paper proposes an optimization model for scheduling project activities holistically, that takes into account multimode activities, the time-cost trade-off problem, and activities constraints to simulate real environments for repetitive activities in construction projects using the Line-of-Balance scheduling technique. The objective is to minimize the overall cost of the project. This optimization model is tested in a concrete bridge case study